PERANCANGAN SISTEM INFORMASI AKUNTANSI PENGGAJIAN BERBASIS WEB PADA LAUNDRY SEPATU SNEAKLIN BANDUNG - Rida Annurfaida (JAF (Journal of Accounting and Finance), 2020)
The purpose of this research is to design an accounting information system application that processes web-based salary data on Sneaklin Bandung laundry shoes, the method is done using descriptive and experimental methods. Salary data processing performed at Sneaklin Bandung Laundry Shoe is already using a computer, namely using the Microsoft Excel program, this method is still troublesome administrative staff in managing employee salary calculation, employee data, and payroll processes. The design of a web-based payroll accounting information system in Sneaklin Bandung shoe laundry using the PHP and MySQL programming languages is expected to facilitate administrative staff in processing payroll data and managing employee data.